Influence of age on biochemical serum parameters in female alpacas – A retrospective study - Matthias Gerhard Wagener; Max Kornblum; Frederik Kiene; Martin Ganter; Ulrike Teichmann (Heliyon)
The determination of biochemical parameters plays an important role in the veterinary care of alpacas, as it can provide an overview of the integrity and function of various organs and metabolic states. Various reference intervals are available for interpreting biochemical results in alpacas, but physiological variations due to age, sex or season should also be considered. Particularly, information on the influence of age is scarce. In a retrospective study, we examined 17 measured and three calculated biochemical parameters of 21 healthy female alpacas from a research herd over a period of nine years. We found significant positive correlations between age and serum triglycerides, selenium, vitamin E, urea, urea/creatinine ratio, calcium/phosphate ratio and significant negative correlations between age and aspartate aminotransferase activity, calcium and phosphate. However, our results differ to some extent from those found in the literature comparing changes in biochemical parameters between juvenile and adult alpacas. Overall, our data suggest that some biochemical parameters in adult alpacas are subject to physiological changes with age, which should be considered when interpreting laboratory results in this species.